A Peptoid Ribbon Secondary Structure. Issue 19 (9th April 2013) - Crapster, J. Aaron; Guzei, Ilia A.; Blackwell, Helen E.
Abstract : Joining the fold : A series of peptoids, or oligomers of N ‐substituted glycines, adopt a novel secondary structure, designated the "peptoid ribbon". This fold was stable at short chain lengths and in a variety of solvents (both organic and aqueous), and arose from a primary sequence of peptoid monomers designed to enforce an alternating pattern of cis and trans main‐chain amides.